BS EN 2302. Aerospace series. Heat resisting nickel base alloy Ni-Cr20Co3Fe3. Rm ≥ 650 MPa. Sheets and strips, cold rolled. 0, 25 mm < a ≤ 3 mm. (21st November 2019) - British Standards Institution,
No abstract available